2008
DOI: 10.3406/dsedu.2008.1145
|View full text |Cite
|
Sign up to set email alerts
|

La différenciation didactique passive : un essai de définition et d’illustration

Abstract: In this paper we first make some considerations on the notion of scientific model. Against this background, we recontextualize the notion of Expected Performance Distance (Maurice, 2007), by relating this concept to some theoretical qualitative speculations (Hacking, 1989) produced in the Joint Action Theory in Didactics. In doing that, we try to establish a dialectic relationship between some qualitative notions and their mathematical articulation (Hacking, 1989). Then we propose the notion of Didactic Passiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This work was conducted in different theoretical fields. Some works based on "product-research" paradigms have made it possible to analyze the correlations between the behavior of teachers in binary (teacher-knowledge) interaction, in ternary interaction (teacher-pupil-knowledge) and the resulting behaviors (between the interactants), their knowledge and motivation (product) [7]. Other studies, based on methodological approaches, have identified novice and expert teachers [8].…”
Section: Focus On Studies Associated To Student Trainee Competenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…This work was conducted in different theoretical fields. Some works based on "product-research" paradigms have made it possible to analyze the correlations between the behavior of teachers in binary (teacher-knowledge) interaction, in ternary interaction (teacher-pupil-knowledge) and the resulting behaviors (between the interactants), their knowledge and motivation (product) [7]. Other studies, based on methodological approaches, have identified novice and expert teachers [8].…”
Section: Focus On Studies Associated To Student Trainee Competenciesmentioning
confidence: 99%
“…They aim to highlight the processes underlying teaching. It is an epistemology of the action according to which the disposition to act of humans is not only underlying, but encompasses or is situated on the register of the relation between the individual and the medium [7]. In physical education and sport, such a model was tested in France by Durand [9].…”
Section: Focus On Studies Associated To Student Trainee Competenciesmentioning
confidence: 99%